Geochemistry of Struban Bog (STR) peat core from the Outer Hebrides in Scotland - Orme, Lisa C (PANGAEA, 2021)
Geochemistry data of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.
Keywords: C-PEAT; Peatland